Factor Vila and other Haemostatic Variables following Bone Marrow Transplantation - Collins, P; Roderick, A; O’Brien, D; Tuddenham, E; O’Driscoll, A; Chopra, R; Goldstone, A; Newland, A (Thrombosis and Haemostasis, 1994)
Hepatic venocclusive disease causes considerable morbidity and mortality following bone marrow transplantation. There are two hypotheses regarding the aetiology of this syndrome; firstly that changes in plasma coagulation factors and natural anticoagulants lead to a prothrombotic state and secondly that endothelial cell activation stimulates intravascular deposition of fibrin. We have investigated these mechanisms by measuring the changes in proteins C and S and factors VII and X in the post transplant period and by using the plasma concentration of factor Vila as an in vivo marker of potential endothelial cell tissue factor expression. Protein C fell in both allograft and autograft patients but more so in the allografts. Similar results were found for factors VII and X. These changes were predominantly due to hepatic dysfunction induced by the chemo-radiotherapy. Factor Vila levels were unchanged in both the allograft and autograft patients. We conclude that there is no convincing evidence for a procoagulant state following BMT as there are both anticoagulant and procoagulant changes. The absence of any changes in factor Vila levels suggests that tissue factor was not exposed to the general circulation following BMT but does not exclude focal expression at the sites of thrombosis.